Minor ischemic stroke: Triaging, disposition, and outcome - Yaghi, Shadi (Neurol Clin Pract, 2016)
BACKGROUND: Two-thirds of patients with stroke have mild deficits. The optimal triaging of these patients remains unclear. It is crucial to stratify patients based on who needs inpatient vs outpatient evaluation in a cost-effective manner. METHODS: We reviewed the current literature (randomized trials, retrospective studies, case series, and case reports) on minor ischemic stroke and extrapolated evidence-based opinions and future directions on the management of minor ischemic stroke. RESULTS: We provide evidence-based opinions and future directions on the approach to triaging patients with mild deficits based on the early risk of stroke recurrence, feasibility of outpatient diagnostic evaluation, and disabling deficits needing inpatient evaluation by physical and occupational therapy. CONCLUSIONS: Outpatient evaluation of patients with nondisabling minor stroke is potentially cost-effective after excluding large artery atherosclerosis and ensuring a rapid access outpatient evaluation. Larger studies on the cost-effectiveness and safety of this approach are necessary.